2022
DOI: 10.3390/cimb44110356
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Alleviates Lipopolysaccharide-Induced Cell Damage and Inflammation via Regulation of the TLR4/NF-κB Pathway in Bovine Intestinal Epithelial Cells

Abstract: Acute diarrhoea and intestinal inflammation represent one of the most prevalent clinical disorders of milk production, resulting in enormous annual financial damage for the dairy sector. In the context of an unsatisfactory therapeutic effect of antibiotics, the natural products of plants have been the focus of research. Quercetin is an important flavonoid found in a variety of plants, including fruits and vegetables, and has strong anti-inflammatory effects, so it has received extensive attention as a potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Another study demonstrated that Nobiletin upregulates PPARG, PPARA, and CXCL8 levels, while inhibiting MMP9 expression and suppressing the release of inflammatory factors TNF-α and IL-6, also achieving anti-inflammatory effects [ 59 ]. Quercetin, a common flavonoid constituent, exhibits potent anti-inflammatory activity by acting as a PPARG agonist to reduce MSU-induced inflammation, block NF-kB activation, and down-regulate the production and expression of IL-1β, IL-6, and MMP9 [ [60] , [61] , [62] ]. Wogonin effectively inhibits migration, invasion, and production of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, MMP-3, and MMP-9) in RA fibroblast-like synoviocytes through the PI3K/AKT/NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that Nobiletin upregulates PPARG, PPARA, and CXCL8 levels, while inhibiting MMP9 expression and suppressing the release of inflammatory factors TNF-α and IL-6, also achieving anti-inflammatory effects [ 59 ]. Quercetin, a common flavonoid constituent, exhibits potent anti-inflammatory activity by acting as a PPARG agonist to reduce MSU-induced inflammation, block NF-kB activation, and down-regulate the production and expression of IL-1β, IL-6, and MMP9 [ [60] , [61] , [62] ]. Wogonin effectively inhibits migration, invasion, and production of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, MMP-3, and MMP-9) in RA fibroblast-like synoviocytes through the PI3K/AKT/NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin has also been reported to mitigate Pseudomonas aeruginosa -induced acute lung inflammation by decreasing the production of proinflammatory cytokines such as IL-1β, IL-6, and TNF-α [ 37 ]. Furthermore, quercetin treatment has been shown to notably lower the mRNA expression levels of proinflammatory cytokines (TNF-α, IL-1β, and IL-6) in lipopolysaccharide (LPS)-induced bovine intestinal epithelial cells (BIECs) [ 38 ]. We examined the changes in mRNA expression of inflammatory factors ( Il-1β , Il-6 , Il-8 , Il-10 , Il-18 , and Tnf-α ) in G. parasuis -infected mice, both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A potential application of QUE in treating bovine viral diarrhoea virus infection has been explored in Madin–Darby bovine kidney cells (MDBK) [ 48 ]. Likewise, QUE’s anti-inflammatory potential has been demonstrated in bovine intestinal epithelial cells (BIECs) [ 49 ] and mammary epithelial cells (BMECs) [ 50 ]. The above-mentioned studies provided important molecular results to disentangle QUE’s mechanism of action in cattle, thus increasing the fundamental knowledge that is necessary to introduce QUE-supplemented feed in farming practice.…”
Section: Discussionmentioning
confidence: 99%